"I should be doing more for my parent:" Chinese adult children's worry about performance in providing care for their oldest-old parents. (22nd October 2015) - Liu, Jinyu; Bern-Klug, Mercedes
ABSTRACT: Background: In China, as is the case in most of the world, family is the largest source of support for frail older adults. Confucian filial piety expectations hold children-in particular sons-responsible for the care of aging parents in China. During the course of caregiving, in addition to positive feelings, the caregiver may feel overwhelmed, entrapped, and worried about their performance, which can have negative health consequences. The purpose of this exploratory study is to examine one dimension of caregiver burden "worry about performance" (WaP) and investigate whether variables inspired by Pearlin's Stress Process Model help to explain the variation of WaP, so that at-risk caregivers can be identified and supported. Methods: Multiple regression was used to analyze CLHLS data from 895 Chinese adult children providing care for their oldest old parent in eight coastal provinces in China. WaP was measured by two items from the Zarit Burden Inventory. Independent variables representing concepts from Pearlin's Stress Process Model and control variables were included in the models. Results: Compared to a model of control variables only, using independent variables inspired by Pearlin's Stress Process Model increased the ability to explain the variation in WaP by three fold to 14%. The following variables increased WaP: parent's IADL level, the amount of time spent caregiving, being a daughter, reporting an emotionally close relationship with the parent, sharing a residence with the parent. Conclusion: Despite not being able to fully operationalize Pearlin's Model with this dataset, analyzing variables that represent concepts from the model was useful in increasing the ability to explain the variation in WaP. Results suggest that caregiver support directed at daughters may be particularly beneficial.